Cognitive deficit and depressive symptoms in a community group of elderly people: a preliminary study - Claudia Silberman; Carolina Souza; Fábio Wilhems; Leticia Kipper; Vivian Wu; Cesar Diogo; Marcelo Schmitz; Airton Stein; Márcia Chaves (Universidade de São Paulo, 1995)
Since the number and proportion of old people increases worldwide, health professionals and systems should be made aware and prepared to deal with their problems. Cognitive deficit and symptoms of depression are commom among the elderly, and may occur in relation to various risk factors such as health conditions and psychosocial variables. In order to study cognitive deficit and the presence of signs and symptoms of depression, 62 elderly community subjects enrolled at a Community Health Unit in Porto Alegre, southern Brazil, were interviewed. They were evaluated by means of the Mini Mental State Exam, the Montgomery-Asberg Depression rating scale, and a questionnaire on health conditions, living arrangements and social variables. Higher levels of symptoms of depression were observed among subjects exposed to major risk factors for cerebrovascular diseases (diabetes and coronary disease), while impaired cognitive performance was seen among individuals who could not count on the presence of a confidant (social network variable). The results suggest that the early identification of major risk groups among old people can help to prevent institutionalization and keep individuals in the community. Com o objetivo de avaliar déficit cognitivo e presença de sinais e sintomas depressivos, 62 idosos registrados numa Unidade de Saúde Comunitária em Porto Alegre/RS foram entrevistados em suas casas. Foram avaliados pelo Mini Exame do Estado Mental (Mini Mental State), pela escala de Montgomery-Asberg, e por um questionário sobre condições de saúde, moradia e outras variáveis de vínculos sociais. Níveis mais altos de sintomas depressivos foram observados entre os idosos expostos a fatores de risco maiores para doença cérebro-vascular (diabete e doença coronariana), enquanto que pior desempenho cognitivo foi encontrado nos sujeitos que não contavam com um confidente (variável da rede social). Os resultados sugeriram que a identificação precoce dos grupos idosos de risco pode auxiliar na prevenção de problemas sociais e de saúde, mantendo os indivíduos na comunidade.